ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) UNTUK MENINGKATKAN KINERJA MANAJERIAL PADA PT. BUMI SELARAS ASRI (GOLDEN SPRING DAN MEETING POINT) MANADO - Hondro, Dione Livia; Budiarso, Novi; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
TQM is a concept or approach of management accounting in maximizing competitiveness through continuous improvement and involving all levels of organization in the company. Managers have an important role in helping the company achieve its goals. The purpose of this research is to find out and analyze the concept of Total Quality Management and its application in PT. Bumi Selaras Asri Manado in an effort to improve managerial performance. The type of research used is qualitative descriptive. Data collection techniques use observations, interviews and documentation. Based on the results of research conducted showed that PT. Bumi Selaras Asri Manado is very concerned about the quality of both its human resources and the quality of the products produced. The existence of one element of TQM that needs to be improved is education and training, while for other elements have been applied well in the company so as to improve managerial performance in it.